A comprehensive analysis of food insecurity in the drought-prone rural areas of Tigray - Tewelde Gebre; Zenebe Abraha; Amanuel Zenebe; Woldegebrial Zeweld (BMC, 2024)
Abstract Background The number of globally food-insecure people is increasing since 2017. Sub-Saharan Africa has the highest proportion of severely food-insecure people in the world. Tigray region of Ethiopia is one of the food-insecure regions, which, over the past many decades has been affected by recurrent food insecurities. In the drought-prone rural areas of Tigray, many people are living under the condition of chronic hunger. Proper food security studies are vital for proper intervention mechanisms. Yet, previous food security studies have rarely addressed the four pillars of food security: availability, access, utilization, and stability. In this study, all components are duly considered to assess the food insecurity status in the drought-prone rural areas of Tigray, Ethiopia. Of the 34 rural districts in Tigray, 363 households from three drought-prone rural districts were studied. Results Household Food Insecurity Access Scale and Food Insecurity Experience Scale were adapted to measure the food availability, access to food, and stability components of food security; and, Household Dietary Diversity Score (HDDS), Food Consumption Score (FCS), mid-upper arm circumference, and Bitot's spot were used to analyze the food utilization aspect. Findings show that 68% of the studied community frequently ate less food than they felt they needed and 82.1% of the households have experienced hunger because of lack of food. The study rural districts were unconnected to road networks; hence, 87.9% of the elderly and 20.4% of the women and girls had no access to food markets. Regarding the food utilization, 81.5% of the studied households had poor FCS; and the average HDDS and FCS for the study areas were 2.47 and 18.9, respectively. The prevalence of Global acute malnutrition, severe acute malnutrition (SAM), and moderate acute malnutrition (MAM) for 6-59 months of age children in the study areas were 50.3, 4.2, and 46.1%, respectively. More notably, the prevalence of SAM for children from the food-insecure households was 21.2%. The prevalence of MAM for pregnant and lactating women (PLW) in the study areas was 59.5. Further, the prevalence of Bitot's spot among 6-59 months of age children was 1.9%. On the other hand, all the rural households had anxiety about their future food demands. Conclusion The rural households living in the studied areas were critically food-insecure. All the measurements implied that the food insecurity situation in the study areas was unacceptably worrisome and life-threatening. This calls for an instant action to avert the occurrence of famine and starvation in the drought-prone rural areas of Tigray region. Thus, interventions should primarily target the vulnerable rural people and need to be planned based on attaining food availability first rather than concurrently addressing all components of food security. Further, due emphasis should be given to diversifying livelihood strategies of the vulnerable villagers.